Kroppens komplekse videnskabelighed. Nye perspektiver på alternativ behandling - Johannesen, Helle (Tidsskriftet Antropologi, 2019)
The numerous conceptions of the body exposed in alternative therapies challenge traditional, Western, biomedically dictated conceptions of the body, disease and healing. The apparent heterogenity could lead to a discharge of alternative body concepts and related therapeutic interventions, but as a large portion of patients experience effect of a variety of alternative treatments, the need for a conceptual framework encompassing heterogenity at several logical levels emerges. For this purpose the author proposes the concept of “the complex body”, in which cultural, social, and natural features are recognized as integral aspects of the individual body, treatment, and the healing process. The body is conceptualized as a complex field of potentials, to be explicated and unfolded in interaction with specific therapeutic concepts and techniques. Underlying the obvious variety within alternative therapies, a common focus on the body as structure, disease as de-structuration, and treatment as re-structuration is revealed. Treatments are rarely aimed at destruction of disease agents or pathologies, but most often aim at a general strengthening - re-structuring - of the patient, biochemically, physiologically, mentally, culturally or socially. Examples from reflexology, biopathy and kinesiology support the validity of a concept of the complex body, which leads to a reconsideration of scientific and scholarly approaches to evaluation of effects of alternative therapies.